Application of Agreement Principles in Land Procurement for Development Public Interest - Sri Hajati (Yuridika, 2019)
The legal issues of this research consist of the application of the consensualism principle in land procurement for development for the sake of public interest. The method of this research is normative legal research by applying statute approach, conceptual approach. The results of this research: there is deviation in the enforcement of the consensualism principle in Article 66 paragraph (4) of Act Number 2 of 2012 which determines that deliberation towards consensus is not only in a form of compensation, is contrary to Article 37 paragraph (1) and (2) of Act Number 2 of 2012 - which stipulates that deliberation is conducted in determining the form and/or the amount of compensation. The provision on consignment or deposit of the compensation at the court is contrary to the consensualism principle because it is conducted without the basis of mutual agreement, and it is against the essence of deliberation which requires consensus.